Towards a measurement of smart and sustainable cities (Publicaciones en Ciencias y Tecnología, 2022)
The term Smart or Sustainable City refers to a global trend that corresponds to the use of information technologies to transform cities into more liveable, viable and sustainable areas for their inhabitants. This article documentarily analyses several measurement models from different countries; ISO/IEEE standards, degrees of maturity, sustainable and inclusive development, environmental improvements, urban intelligence metrics, a "Smart Dashboard", as well as performance indicators to evaluate the success and progress of smart city projects. It analyses the results and provides a comparison of the measurement models and metrics evaluated, to assist in the development of policies and initiatives, to guide economic growth and social development of rural and urban communities. To propose a strategic guide that can be used for the design of smart and sustainable projects, to try to improve the quality of life of citizens.
Keywords: sustainable development; urban development; information society; urban areas; economic and social development; smart cities